Strategic outsourcing: a lean tool of healthcare supply chain management - Guimarães, M.; Crespo de Carvalho, J. (Strategic Outsourcing: An International Journal, 2013)
Purpose – Considering lean thinking inside and beyond the organisation's boundaries, in the extended supply chain, this paper aims to fill a literature gap clearly stating some outsourcing practices as lean practices and establishing a deployment evolution parallel between both practices. Design/methodology/approach – A literature review was carried out collecting cases of lean deployment in healthcare, from both scientific and grey literature. Cases were classified according to lean deployment taxonomy in healthcare settings, showing some differences in lean journey stages in 15 countries. Findings – There is an alignment between SCM thinking in healthcare and lean thinking that places a SCM decision as outsourcing as a lean practice serving not only strategic intent but solving operational efficiency. There is a match between different outsourcing drivers (transactional, strategic and transformational) and lean maturity levels. The main constraint to deployment of both lean and outsourcing practices are cultural differences. Practical implications – Understanding lean and outsourcing different deployment maturity levels under the national cultural umbrella can open new perspectives to study lean sustainability factors and better outsourcing relationships in healthcare organisations. Originality/value – This paper presents a merger between the state-of-the art of both lean and outsourcing practices in healthcare settings and suggests an outsourcing and lean evolving pathway.